Consumption of Cod Liver Oil-enriched Vernonia amygdalina Leaf-based Diet Promoted Wound Healing in Wound-inflicted Type 2 Diabetic Wistar Rats - Soji-Omoniwa, Omolola; Adebayo, Samuel Opeyemi; Ayinde, Rukky Oluwatoyin; Oyeniyi, Abisodun Felicia; Adeleye, Darasimi Aderonke; Ezechukwu, Tracy-Allen; Chinedum, Chiemela; Emeje, Erhime Favour; Alebiosu, Onaopemipo; Ajibola, Olawunmi Esther; Adeniyi, Precious Omolara; Adebiyi, Adekunle Ayodeji; et al. (AlQalam Journal of Medical and Applied Sciences, 2022)
Background. Diabetes mellitus is an important factor that contribute to non-healing chronic wound and 2 out of 10 diabetic patients in Nigeria present with diabetic foot ulcer. The aim of this study was to evaluate the effect of cod liver oil-enriched Vernonia amygdalina leaf-based diet (CLVA) on wound healing in wound-inflicted type 2 diabetic rats. Methods. Thirty-six albino rats were randomly assigned into 6 groups namely; control (C), diabetic untreated control (DC), reference drug control (RD), 10 % CLVA, 20 % CLVA and 30 % CLVA. All the groups except C were diabetic rats inflicted with wound, while C were non diabetic rats inflicted with wound. Groups C, DC and RD were fed diet without cod liver oil (CLO) and Vernonia amygdalina (VA) leaves. The last 3 groups were fed 10, 20 and 30 % inclusion VA leaves and CLO in their diet. Feeding was done ad libitum for 14 days. Wound areas images, fasting blood glucose (FBG), Serum insulin, nitric oxide (NO) concentrations, wound contraction rate, interleukins-1β (IL-1β ), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), nuclear factor-kappa B (NF-κB) and vascular endothelial growth factor (VEGF) were monitored. Results. Results showed significant reduction (p < 0.05) in FBG, insulin, NO, IL-1β, IL-6 and TNF-α concentrations of rats fed on 10, 20 and 30 % to DC, while VEGF increased significantly (p < 0.05). Expression of iNOS, COX-2 and NF-κB were down-regulated in rats fed on all CLVA inclusion levels. Wound contraction rate increased significantly (p < 0.05) at the various inclusion levels compared to DC, with wound area images showing progressive wound closure in CLVA-fed groups. Conclusion. Consumption of CLVA promoted wound healing in wound-inflicted diabetic rats.